Small spheroids for head and neck cartilage tissue engineering - Reutter, Sven; Kern, Johann; Jakob, Yvonne; Rotter, Nicole; Gvaramia, David (Scientific reports, 2024)
The demand for cartilage reconstruction in the head and neck region arises frequently due to trauma, malignancies, and hereditary diseases. Traditional tissue engineering produces cartilage from a small biopsy by combining biomaterials and expanded cells. However, this top-down approach is associated with several limitations, including the non-uniform distribution of cells, lack of physiological cell-cell and cell-matrix interactions, and compromised mechanical properties and tissue architecture. The capacity of cells to aggregate into microtissues enables an alternative bottom-up approach to producing cartilage with or without further scaffolding support. Here we explored the optimal conditions for obtaining small spheroids from head and neck cartilage tissues. We used chondrocytes (CCs) and chondroprogenitors (CPCs) isolated from auricular and nasoseptal cartilage to prepare spheroids using ultra-low attachment (ULA) plates or micromass cultures. Different cell densities were tested to estimate the minimal cell number required for optimal spheroid formation. Furthermore, we evaluated the influence of key chondrogenic cytokines, such as transforming growth factor (TGF)-β, connective tissue growth factor (CTGF), and insulin-like growth factor (IGF)-1, on spheroid morphology and the production of cartilage extracellular matrix (ECM) components. Spheroids expressing cartilage markers were formed with 2.5 × 104 cells in a commercially available chondrogenic differentiation medium on ULA plates but not in conventional micromass cultures. Differences were seen in auricular and nasal spheroids with respect to growth patterns and response to cytokine composition. Auricular spheroids were larger and showed size increase in culture, whereas nasal aggregates tended to shrink. Cytokines differentially influenced spheroid growth, and ECM structure and composition. Under all tested conditions, both spheroid types generated one or more cartilage ECM components, including elastin, which was also found in nasal spheroids despite their hyaline origin. Our results suggest that spheroid cultures can offer a viable approach to generating mature cartilage tissue without a biomaterial scaffold. Furthermore, nasal CCs and CPCs can be used to generate elastic cartilage. The findings of the study provide technical insights toward the goal of obtaining cartilage microtissues that can be potentially used for reconstructive procedures of HNC cartilage defects.
Gesehen am 27.03.2025